Exploring the Effect of Destination Image on Revisit Intention via Satisfaction and Place Attachment: Evidence from Pujon Kidul Tourism Village Indonesia - Ardik Praharjo; Rahmad Wijaya; Khusnul Rofida Novianti (International Journal of Small and Medium Enterprises and Business Sustainability, 2025)
Tourist loyalty, particularly revisit intention, has been widely acknowledged as a key determinant of destination competitiveness and long-term sustainability. This study aims to investigate the antecedents of revisit intention by examining the role of destination image, satisfaction, and place attachment. Destination image has often been regarded as a fundamental factor influencing tourists’ perceptions and behavioral outcomes, while satisfaction and place attachment serve as critical mediators that strengthen the intention to revisit. A quantitative approach was employed through a survey of visitors to Pujon Kidul Tourism Village, an emerging rural tourism destination in Malang Regency, Indonesia. Data analysis was conducted using the Partial Least Squares (PLS) method to evaluate the structural relationships among the variables. In developing the research framework, theories and empirical findings from reputable journal articles were systematically reviewed to ensure theoretical rigor and relevance. The results of this study reveal that destination image exerts a significant positive influence on revisit intention, both directly and indirectly, through the mediating effects of satisfaction and place attachment. Specifically, a favorable destination image enhances visitor satisfaction, which subsequently fosters a stronger emotional bond with the place, thereby increasing the likelihood of repeat visitation. This study contributes to the literature by integrating destination image, satisfaction, and place attachment into a comprehensive model of tourist loyalty. From a managerial perspective, the findings provide practical insights for destination managers and policymakers to improve image-building strategies, enhance visitor experiences, and cultivate stronger attachments that encourage sustainable tourism development